2020
DOI: 10.3390/w12030801
|View full text |Cite
|
Sign up to set email alerts
|

Quantile Mapping Bias Correction on Rossby Centre Regional Climate Models for Precipitation Analysis over Kenya, East Africa

Abstract: This study uses the quantile mapping bias correction (QMBC) method to correct the bias in five regional climate models (RCMs) from the latest output of the Rossby Center Climate Regional Model (RCA4) over Kenya. The outputs were validated using various scalar metrics such as root-mean-square difference (RMSD), mean absolute error (MAE), and mean bias. The study found that the QMBC algorithm demonstrates varying performance among the models in the study domain. The results show that most of the models exhibit r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…The two main projections utilized are drawn from Tier 1 ScenarioMIP: SSP2-4.5 and SSP5-8.5. Following the recommendations of previous studies (e.g., [57,[81][82][83][84][85]), this employs MME of CMIP6 for projection of extreme events over the study area. Many studies have remarked on the robustness of MME as compared to individual models due to cancellation of intermodel biases [59].…”
Section: Discussionmentioning
confidence: 99%
“…The two main projections utilized are drawn from Tier 1 ScenarioMIP: SSP2-4.5 and SSP5-8.5. Following the recommendations of previous studies (e.g., [57,[81][82][83][84][85]), this employs MME of CMIP6 for projection of extreme events over the study area. Many studies have remarked on the robustness of MME as compared to individual models due to cancellation of intermodel biases [59].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have pointed out the simulated precipitation over Uganda and the Greater Horn of Africa depends on the boundary layers, the model horizontal resolution, and the parameterization schemes [51][52][53][54]. In fact, in a recent study over East Africa [55] established that the biases in GCMs are not fully corrected to resemble observed patterns, despite the implementation of various robust statistical methods such as quantile approach. Even Regional Climate Models (RCMs) which are of spatially finer resolution than the GCMs were found to be largely biased in reproducing the East African climatology [56].…”
Section: Discussionmentioning
confidence: 99%
“…The KMD dataset was therefore corrected using the Quantile Mapping bias correction algorithm technique, which has been widely used for correction of precipitation datasets [57][58][59] and has demonstrated high performances in arid and semi-arid areas [33,60]. In particular, the work of Ringard et al demonstrated its usefulness for satellite-derived datasets correction in scarce observed data contexts [61].…”
Section: Correction Through the Quantile Mapping Methodsmentioning
confidence: 99%
“…The relationship between large-scale weather systems and local climate varies from region to region, making necessary to evaluate and correct them at local scale [23,24], but the scarcity of land surface observation is one of the greatest difficulties in assessing dataset performances [25]. Previous studies have tried to assess the performance of satellite-derived and model-derived datasets in East Africa [26][27][28][29][30][31][32], in particular in Kenya [33][34][35], in order to address the lack of data from land-based meteorological stations. However, these studies have a more regional perspective rather than a local focus, and further investigation on their use at local scale is needed.…”
Section: Introductionmentioning
confidence: 99%